Magnetofluorescent micellar complexes of terbium(iii) as potential bimodal contrast agents for magnetic resonance and optical imaging. Issue 14 (19th January 2015) - Harris, Michael; Carron, Sophie; Vander Elst, Luce; Laurent, Sophie; Muller, Robert N.; Parac-Vogt, Tatjana N.
Abstract : Micellar nano-aggregates containing Tb(iii ) have been evaluated as a single lanthanide bimodal contrast agent for magnetic resonance and optical imaging. Abstract : Terbium(iii ) was coordinated to four novel 1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid (DOTA) amphiphilic bisamide ligands. The complexes were assembled into mono-disperse micellar nano-aggregates and for the first time Tb III has been evaluated as a single lanthanide negative bimodal contrast agent for MRI/OI. The complexes show characteristic Tb III emission with quantum yields reaching 7.3% and transverse relaxivity r 2 per Tb III micelle at 500 MHz and 310 K reaches maximum values up to 60 s −1 micelle −1 . The efficient T 2 relaxation at high magnetic field strengths is sustained by the increased rotational correlation time of the nano-aggregates and high magnetic moment of the terbium ion.